2016
DOI: 10.1002/jclp.22372
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion‐Driven Impulse Control Difficulties in the Relation Between Social Anxiety and Aggression

Abstract: Results highlight the potential utility of targeting emotion-driven impulse control difficulties to decrease aggression among socially anxious individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(80 reference statements)
2
8
0
2
Order By: Relevance
“…Thus, for example, we were able to demonstrate that across the globe SAD disorder persistence is particularly highly associated with lower education, episode persistence is particularly associated with being a student, while both disorder and episode persistence are associated with being a homemaker. While it has previously been demonstrated that SAD more likely follows other anxiety disorders, and precedes depression [ 1 ], here we provide novel data on the comorbidity of SAD with impulse control disorders; this is valuable given that a link between social anxiety and aggression has been posited in the animal and clinical literature [ 28 , 29 ]. It is notable that in both lifetime and 12-month SAD, SAD begins earlier in only 31.4–35.4% of cases of comorbid anxiety disorder, due to the common comorbidity with specific phobia which has the earliest onset of the anxiety disorders, but SAD begins earlier in 48.8–80.9% of cases of comorbid mood disorder, substance use disorder, or impulse control disorder.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, for example, we were able to demonstrate that across the globe SAD disorder persistence is particularly highly associated with lower education, episode persistence is particularly associated with being a student, while both disorder and episode persistence are associated with being a homemaker. While it has previously been demonstrated that SAD more likely follows other anxiety disorders, and precedes depression [ 1 ], here we provide novel data on the comorbidity of SAD with impulse control disorders; this is valuable given that a link between social anxiety and aggression has been posited in the animal and clinical literature [ 28 , 29 ]. It is notable that in both lifetime and 12-month SAD, SAD begins earlier in only 31.4–35.4% of cases of comorbid anxiety disorder, due to the common comorbidity with specific phobia which has the earliest onset of the anxiety disorders, but SAD begins earlier in 48.8–80.9% of cases of comorbid mood disorder, substance use disorder, or impulse control disorder.…”
Section: Discussionmentioning
confidence: 93%
“…Adolescents rated the extent to which they experience the specified statements on a scale from 1 ( almost never ) to 5 ( almost always ). Example items are as follows: “When I’m upset, I have difficulty controlling my behaviors” and “When I’m upset, I feel out of control.” This six-item subscale has been used in several studies using community samples (Dixon, Tull, Lee, Kimbrel, & Gratz, 2017). Internal consistency in the current sample was alpha of .83 for Time 1 and .81 for Time 2.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, difficulties in emotional impulse control have been linked to substance use (e.g., Dingle et al, 2018), aggression (e.g., Dixon et al, 2017), and other various types of symptomatology (e.g., Cheung & Ng, 2019;Fergus & Bardeen, 2014). Other studies (e.g., Dixon et al, 2017;McLaughlin et al, 2011) also emphasize the importance of ER abilities in the development and course of various psychopathological symptoms.…”
mentioning
confidence: 98%
“…For example, problems identifying emotions (i.e., emotional clarity) have been associated with symptoms of social anxiety, depression, and maladaptive behaviors such as alcohol use and binge eating (Vine & Aldao, 2014). Similarly, difficulties in emotional impulse control have been linked to substance use (e.g., Dingle et al, 2018), aggression (e.g., Dixon et al, 2017), and other various types of symptomatology (e.g., Cheung & Ng, 2019;Fergus & Bardeen, 2014). Other studies (e.g., Dixon et al, 2017;McLaughlin et al, 2011) also emphasize the importance of ER abilities in the development and course of various psychopathological symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation